BIFURCATE FLOWER TRUSS: a novel locus controlling inflorescence branching in tomato contains a defective MAP kinase gene - Silva Ferreira, Demetryus; Kevei, Zoltan; Kurowski, Tomasz J.; de Noronha Fonseca, Maria Esther; Mohareb, Fady R.; Boiteux, Leonardo S.; Thompson, Andrew J. (Oxford University Press, 2018)
A mutant line, bifurcate flower truss (bif), was recovered from a tomato breeding program. Plants from the control line LAM183 produced a mean of 0.16 branches per truss, whereas the value for bif plants was 4.1. This increase in branching was accompanied by a 3.3-fold increase in flower number and showed a significant interaction with exposure to low temperature during truss development. The LAM183 and bif genomes were resequenced and the bif gene was mapped to a 2.01 Mbp interval on chromosome 12; all coding region polymorphisms in the interval were surveyed and five candidate genes displaying altered protein sequences were detected. One of these genes, SlMAPK1, encoding a MAP kinase, contained a leucine-to-stop codon mutation predicted to disrupt kinase function. SlMAPK1 is an excellent candidate for bif because knock-out mutations of an Arabidopsis orthologue MPK6 were reported to have increased flower number. An introgression browser was used to demonstrate that the origin of the bif genomic DNA at the BIF locus was Solanum galapagense and that the SlMAPK1 null mutant is a naturally occurring allele widespread only on the Galápagos Islands. This work strongly implicates SlMAPK1 as part of the network of genes controlling inflorescence branching in tomato.
Keywords: Bifurcate flower truss; Branching; Genome resequencing; Inflorescence architecture; Low temperature; MAP kinase; Solanum galapagense; Solanum lycopersicum